2017
DOI: 10.1038/bmt.2017.100
|View full text |Cite
|
Sign up to set email alerts
|

Idarubicin-intensified haploidentical HSCT with GvHD prophylaxis of ATG and basiliximab provides comparable results to sibling donors in high-risk acute leukemia

Abstract: We designed a novel haploidentical hematopoietic stem cell transplantation (haplo-HSCT) system using idarubicin (IDA) intensified conditioning regimens and combination of antithymocyte globulin and basiliximab for GvHD prophylaxis. The outcomes of 110 high-risk acute leukemia patients undergoing haplo-HSCT were compared with 69 contemporaneous high-risk patients receiving HLA-matched sibling transplantation using uniform IDA-intensified regimens. The relapse incidence of haplo-HSCT was 23.4%, and 3-year overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 43 publications
3
35
1
Order By: Relevance
“…A cohort of 98 consecutive patients with high-risk acute leukemia who underwent their first allo-HSCT using IDA-intensified conditioning regimens from January 2012 to January 2017 at the Institute of Hematology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, were included in this retrospective study. We classified patients as high risk at diagnosis following the criteria in our previous reports [9][10][11][12]. The definition of high-risk AML were no response to induction chemotherapy, relapse within 6 months after induction or consolidation therapy, relapse within 6 months after induction therapy that could not be relieved using the original induction therapy, 2 relapses or relapse after auto-HSCT, unfavorable cytogenetics, or a history of preceding neoplasia and/or chemotherapy in no remission (NR).…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…A cohort of 98 consecutive patients with high-risk acute leukemia who underwent their first allo-HSCT using IDA-intensified conditioning regimens from January 2012 to January 2017 at the Institute of Hematology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, were included in this retrospective study. We classified patients as high risk at diagnosis following the criteria in our previous reports [9][10][11][12]. The definition of high-risk AML were no response to induction chemotherapy, relapse within 6 months after induction or consolidation therapy, relapse within 6 months after induction therapy that could not be relieved using the original induction therapy, 2 relapses or relapse after auto-HSCT, unfavorable cytogenetics, or a history of preceding neoplasia and/or chemotherapy in no remission (NR).…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…The definition of hematopoietic engraftment was similar to that reported previously [9][10][11][12]. Chimerism was typically evaluated in recipient BM or whole peripheral blood without separation usually on days +30, +90, +180, +270, and +360 after transplantation.…”
Section: Hematopoietic Engraftment and Transplant-related Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Lie et al used a combination of fludarabine, cytarabine, TBI, Cy, and etoposide for conditioning in the haplo-setting and demonstrated that intensified conditioning decreased the 5-year relapse rate from 33.9 to 27.3%, and it may be a better approach for refractory and acute leukemia of ambiguous lineage [ 84 86 ]. Idarubicin-intensified haplo-HSCT introduced by the Wuhan Union group improved the dismal prognosis of pre-transplant MRD and yielded a 3-year DFS of 47.3% [ 87 ].…”
Section: Introductionmentioning
confidence: 99%